A wavelet-based approach to testing shari’ah-compliant stock market contagion:evidence from the ASEAN countries - Saiti, Buerhan; Dewandaru, Ginangar; Masih, Mansur (INSI Publications, 2013)
Recently there has been a heightened global concern over ‘contagion’ in the conventional financial markets. Our study is motivated by the desire to test empirically whether this contagion is reflected in the fast growing Islamic financial markets as well. This study is the first attempt at testing whether there has been any contagion among the Shari’ah-compliant stock markets during the most recent international financial crisis: the US subprime crisis of 2008, with the application of a technique known as ‘wavelet approach’ which has been very recently imported to finance from engineering science. We analyse the daily data covering the period from June 2006 to August 2009 for the stock market indices of the original ASEAN countries plus Australia and USA such as, NYSE COMPOSITE (US), MSCI Islamic (Australia), MSCI Islamic (Singapore), FTSE Bursa EMAS Shari’ah (Malaysia), Jakarta SE Islamic (Indonesia), MSCI Islamic (Thailand) and MSCI Islamic (Philippines). Our findings based on the time-scale decomposition property of wavelet analysis tend to indicate that in all cases of selective Shari’ah-compliant stock markets the changes in the wavelet correlation coefficients are insignificant at all time scales during the US subprime crisis. The changes observed in wavelet correlation coefficients are insignificant due to overlapping of confidence intervals implying that there is no clear evidence of contagion at all time scales. These findings are plausible and intuitive and have implications for the Shari’ah-compliant stock markets in terms of asset allocation strategy of risk managers and for policymakers’ optimal policy response to a crisis.